Social capital, affect balance and personal well-being among teachers in Israel and Palestine. Issue 8 (17th November 2018) - Veronese, Guido; Pepe, Alessandro; Dagdukee, Jamal; Yaghi, Shaher
ABSTRACT: Informed by a perspective centred on psychological health and well-being, the present research investigated whether teachers' overall well-being was influenced by their affect balance, as well as the extent to which both affect and well-being are influenced by social capital, in conflict-ridden areas such as the occupied Palestinian Territories (Gaza Strip and West Bank). The study involved three cohorts of Palestinian teachers working in Israel, Gaza and the West Bank, respectively ( N = 153). Dynamics of social exclusion, religious difference, educational disparity, poor educational standards and a lack of opportunity are factors affecting Palestinian teachers in both Israel and the occupied Palestinian territories. The results supported the hypothesis that emotional balance directly influences teachers' well-being. Teachers with higher levels of positive affect reported greater personal well-being than those with higher levels of negative affect. Social capital also positively influenced teachers' personal well-being, both directly, and indirectly by fostering positive emotions. These results suggest that availability of community resources plays a key role in promoting teachers' well-being.